2008
DOI: 10.1038/sj.bjc.6604172
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of VEGF and EGFR predicts complete tumour response in rectal cancer treated with preoperative radiotherapy

Abstract: The ability to predict complete pathologic response or sensitivity to radiation before treatment would have a significant impact on the selection of patients for preoperative radiotherapy or chemo-radiation therapy schedules. The aim of this study was to determine the value of epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), p53, Bcl-2 and apoptosis proteaseactivating factor-1 (APAF-1) as predictors of complete pathologic tumour regression in patients undergoing preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 60 publications
(57 reference statements)
2
49
0
2
Order By: Relevance
“…Furthermore, low levels of VEGFR-2 expression in cancer cells after therapy were associated to RTA (P = .007). Zlobec et al [30] in a cohort of 104 patients with LARC treated with preoperative radiotherapy alone found that the combined analysis of VEGF and EGFR was predictive of ypCR, with the subgroup of cases with VEGF-positive and EGFR-negative tumors being unresponsive to radiation therapy. However, in such a translational study no patient was treated with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low levels of VEGFR-2 expression in cancer cells after therapy were associated to RTA (P = .007). Zlobec et al [30] in a cohort of 104 patients with LARC treated with preoperative radiotherapy alone found that the combined analysis of VEGF and EGFR was predictive of ypCR, with the subgroup of cases with VEGF-positive and EGFR-negative tumors being unresponsive to radiation therapy. However, in such a translational study no patient was treated with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that VEGF-positive rectal cancer was resistant to radiotherapy (Zlobec et al, 2008). Nestin, a class VI intermediate filament protein, has recently received attention as a marker for detecting newly formed endothelial cells (Teranishi et al, 2007).…”
mentioning
confidence: 99%
“…Так, I. Zlobec и соавт. [60] провели ис-следование, в которое включили 104 пациента с резектабельным инвазивным раком прямой кишки (гистологически -аденокар-цинома). Отбирали пациентов с опухолью Т2, Т3 и Т4 (размером от 3 до 5 см).…”
Section: комбинированное лечение нижнеампулярного рака прямой кишкиunclassified